ANALYSIS OF BANKING SOUNDNESS USING CAMEL METHOD (STUDY OF PT. BANK MANDIRI-PERSERO TBK FROM 2012 â€“ 2014) - Saiya, Sari I. J.; Pandowo, Merinda (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Bank is a financial institution that acts as the intermediary of Surplus Spending Unit (SSU) and Deficit Spending Unit (DSU). Bank must be managed professionally by applying the prudential principles in order to achieve the objectives, while also looking for the development of the society where the bank performs its activities. In this research, the financial statements such as the Balance Sheet, and the Income Statement (Profit and Loss Statement) from the period of 2012 to 2014 will be analyzed by the researcher through CAMEL method. The result shows that PT. Bank Mandiri. in banking industry is predicating healthy. As shown on the result of analysis since in year 2012 until in year 2014 has CAMEL score which followed 94.81; 94.12 and 93.38. Thus PT. Bank Mandiri (Persero) Tbk. should pay more attention in the field of liquidity where in year 2014 the LDR scores decrease about 1% and to increase the liquid, bank should do:Â  (1) Add their own capital as supplement to current assets. (2) Reduce current debts and increase their own capital. (3) Reducing the current debts from the selling of some assets, thus if the liquid still increase then the LDR score would be in good position in accordance with the regulation made by Bank Indonesia (BI). Keywords: banking soundness, liquidity, own capital